Milk recording and herd registration in Ethiopia: An essential step towards genetic improvement for milk production - Tegegne, Azage; Redda, T.; Gebre-Wold, A.; Ketema, H. (Ethiopian Society of Animal Production, 2000)
Genetic improvement for productive traits in livestock, particularly in cattle, has been very slow and insignificant in the country. One of the main reasons for this is lack of well-organized and usable recorded information on the performance of both the indigenous and crossbreds with exotic genotypes to undertake structured selection and breeding programmes. A recording scheme is the basis for information decision-making process at different levels. Recognizing this fact, a number of government institutions, non-government organizations and individuals have attempted to introduce milk-recording systems in Ethiopia. However, these efforts have been scattered and isolated and as such, there has not been a centrally coordinating national body to undertake the leadership in the implementation of such a scheme in a systematic and useful manner. In most instances, data have accumulated over the years with little or no use to the producer, the farm and the nation for management decision making, planning, policy formulation, selection and genetic improvement programs. One important common feature of these recording systems is the least attention given to the indigenous cattle. In this paper, experiences in milk recording in Ethiopia are reviewed and the lessons learnt have been summarized. The need for milk recording and herd registration in Ethiopia is elaborated A proposal to establish a national milk recording and herd registration scheme is presented and discussed A pilot project to test and fine-tune the proposal has been developed for testing by the Smallholder Dairy Development Project (SDDP) of the Ministry of Agriculture using dairy farms under the SDDP. The most important features of this scheme are also described. It has to be understood that the Development of a milk recording scheme is a dynamic process and will have to be upgraded through time in response to changing internal and external circumstances.